2022
DOI: 10.1186/s12958-022-00902-9
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 inhibits human trophoblast cell invasion by upregulating kisspeptin expression through ERK1/2 but not SMAD signaling pathway

Abstract: Background Tightly regulation of extravillous cytotrophoblast (EVT) cell invasion is critical for the placentation and establishment of a successful pregnancy. Insufficient EVT cell invasion leads to the development of preeclampsia (PE) which is a leading cause of maternal and perinatal mortality and morbidity. Transforming growth factor-beta1 (TGF-β1) and kisspeptin are expressed in the human placenta and have been shown to inhibit EVT cell invasion. Kisspeptin is a downstream target of TGF-β1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Therefore, failures in the kisspeptin/Kiss1R signaling system result in hypogonadotropic hypogonadism (3,4). In addition to its hypothalamic action, however, the kisspeptin/Kiss1R system is expressed in a variety of tissues, including the placenta (5,6), although studies on the action of kisspeptin on the placenta are still scarce (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, failures in the kisspeptin/Kiss1R signaling system result in hypogonadotropic hypogonadism (3,4). In addition to its hypothalamic action, however, the kisspeptin/Kiss1R system is expressed in a variety of tissues, including the placenta (5,6), although studies on the action of kisspeptin on the placenta are still scarce (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the placenta is one of the main sources of systemic kisspeptin. Studies have shown that kisspeptin influences the adhesion and implantation of blastocysts and the decidualization and migration of trophoblasts, and regulates the immunological profile and uterine natural killer cells (uNKs) (5,(7)(8)(9)(11)(12)(13)(14)(15)(16)(17), suggesting that faults in its expression in the maternal-fetal interface may be involved in placental disorders (12,18).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that binding KISS-1R with the ligand in the placenta may decrease their expression in syncytiotrophoblast, as in thyrotropin-releasing hormone [ 47 ]. The latest experimental research indicates that transforming growth factor β-1 (TGF β-1) upregulates kisspeptin expression in human extravillous cytotrophoblast cells by inhibiting the ERK1/2 signaling pathway and, in this way, it leads to decreased trophoblast cell invasion [ 48 ]. The process of kisspeptin isoforms formation, as well as its various signaling pathways, are presented in Figure 1 .…”
Section: The Kiss-1 Gene Kisspeptin and Its Signalingmentioning
confidence: 99%
“…The latest in vitro experimental study has shown that TGF-β, which is also expressed in the human placenta and is responsible for the regulation of cellular processes, seems to inhibit human trophoblast cells’ invasion by upregulating kisspeptin expression through the ERK1/2 signaling pathway [ 48 ]. Furthermore, numerous studies have revealed that kisspeptin may restrain the trophoblast growth by activating apoptosis in a dose-depended manner, together with pro-inflammatory cytokines, including tumor necrosis factor α (TNF-α) [ 96 , 97 , 98 ].…”
Section: Role Of Kisspeptin In the Pathogenesis Of Disorders From The...mentioning
confidence: 99%
See 1 more Smart Citation